Infrared spectroelectrochemistry of bacteriochlorophylls and bacteriopheophytins: Implications for the binding of the pigments in the reaction center from photosynthetic bacteria - Mäntele, W. G. (1988)
The IR spectra of the bacteriochlorophyll a and b cations and the bacteriopheophytin a and b anions were obtained by using an IR and optically transparent electrochemical cell. Prominent effects of radical formation on the vibrational spectra were found for bands assigned to the ester, keto, and acetyl C=O groups and for vibrations from macrocycle bonds. The (radical-minus-neutral) difference spectra are compared to the light-induced difference spectra of the primary donor photooxidation and the intermediary acceptor photoreduction in the reaction center of photosynthetic bacteria. Light-induced absorbance changes from bacteriochlorophyll a-containing reaction centers bear striking similarities to the electrochemically induced absorbance changes observed upon formation of bacteriochlorophyll a(+)in vitro. Comparison of the radical formation in vitro in a hydrogen-bonding or a nonhydrogen-bonding solvent suggests an ester C=O group hydrogen bonded in the neutral state but free in the cation state. For the keto C=O group, the same comparison indicates one free carbonyl group. The (anion-minus-neutral) difference spectra of bacteriopheophytin a and b exhibit a single band in the ester C=O frequency range. In contrast, two bands are observed in the difference spectra of the intermediary acceptor reduction in the reaction center of Rhodopseudomonas viridis. The higher frequency band exhibits a sensitivity to (1)H-(2)H exchange, which suggests a contribution from a protonated carboxyl group of an amino acid side chain.